Do Biodegradable Microplastics Threaten Chlorella spp.? First Study in Indonesia Using Leachate Exposure - Azizah, Nur Aini; Hindarti, Dwi; Herawati, Endang Yuli; Nainggolan, Dicky Willy; Sartimbul, Aida (Biotropika: Journal of Tropical Biology, 2025)
Biodegradable plastics are increasingly being promoted as environmentally friendly alternatives to conventional plastics. However, under aquatic conditions, their degradation may remain incomplete, leading to the formation of microplastics and leachates containing potentially toxic compounds. These leachates can threaten aquatic organisms, particularly microalgae, which act as primary producers and form the base of marine food web. Despite these concerns, limited research has examined the sublethal toxicity of biodegradable microplastic leachates on microalgae. This study aimed to evaluate the toxic effects of leachates derived from biodegradable polypropylene (PP) and high-density polyethylene (HDPE) plastics on the growth of the green microalgae Chlorella spp. A 96-hour static toxicity test was conducted under laboratory conditions using a completely randomized design with five concentration levels (0, 0.1, 1.0, 10, and 100 mg/L). The algae were cultured in EDTA-free Walne medium with an initial cell density of 104 cells/mL. Cell density was measured at the end of exposure to determine growth inhibition and calculate the 50% inhibitory concentration (IC50). The results showed a clear concentration-dependent response, with PP leachate exhibiting significantly higher toxicity (IC50 = 0.48 mg/L) compared to HDPE leachate (IC50 = 682.49 mg/L). These findings suggest that the chemical composition and leachability of additives differ among plastic types, influencing their environmental impact. This study highlights the potential ecological risks of biodegradable plastics and emphasizes the need for stricter regulation of additives and comprehensive ecotoxicological assessments.